L’esperienza pionieristica dell’Istituto delle Sordomute Povere di Bologna per l’educazione della sordità - Rossella Raimondo (Studi sulla Formazione)
Thanks to the use of previously unpublished sources, this research examines the IstitutoSordomute Povere di Bologna, which celebrates its one hundred and seventy-ninth birthday this year, to analyse about its management and organisational aspects, as well as its pedagogical and didactic issues. By retracing the traces of its history, preserved in its archives, it is possible to put in evidence the socio-educational farsightedness with which it was conceived a structure that was able to mark a very important turning point in the Bolognese territory, introducing methods and approaches aimed at providing education, instruction and religious training to young deaf girls belonging to poor families from 6 to 14 years of age, saving them from social isolation, illiteracy and the dangers inherent in their destitute condition.